Scoping Review of Universal Design for Learning Principles Embedded in Subjects in Secondary Education - Phelan, Danielle; Maguire, Helen; Finnegan, Clare (European journal of education, 2025)
ABSTRACT To date, much of the research on UDL has focussed on higher education, with a dearth of research surrounding UDL within secondary education. This study aimed to identify the application of the principles of UDL embedded in subjects in secondary education worldwide. The PRISMA ScR methodological framework was employed, and numerical summaries and thematic analysis were utilised to describe the data quantitatively and qualitatively, respectively. Results demonstrate that most of the articles were based in North America, used an intervention study approach and reported positive results on student engagement post‐intervention. While all articles displayed evidence of UDL pedagogical practices, some articles did not specifically identify these practises as UDL. This could suggest that (1) an awareness of UDL as an inclusive pedagogical framework is lacking in current educational research, and/or (2) UDL may be incorporated into teaching practices more frequently than is currently being identified. The findings suggest that future research from a European context may provide novel insight into the operationalisation and potential of UDL in secondary education.